RESETTING VERTICALITY FLARE STACK DENGAN PENGATURAN TEGANGAN GUY WIRE - Sulardi Sulardi; Sabar P. Simatupang; Lukman Lukman (Universitas Lambung Mangkurat, 2021)
The flare stack is an important installation in the oil and gas industry as a tool to burn off-specification gas so as not to harm the environment. The problem faced is that there is a slope on the riser vertical stake so that it exceeds the safe limit (out of tolerance). The purpose of this research is to determine the method of resetting the riser flare stack so that the verticality returns to the uprightness as required by API 521. The method of resetting the verticality flare stack is carried out by adjusting the tension on all guy wire support vertical riser stacks so that each receives a voltage of 1.2 - 1.4 tons and mutually eliminate the stresses that occur when the riser stak gets a load from the outside or as a result of plant operations. The results showed that the guy wire support tension resetting method was proven to be suitable and suitable for use properly and safely with a maximum erection of 145 mm (1/800L) vs. API 521 standard tension maximum of 232mm (1/500L). The results of this study also recommend that the resetting work method that has been proven to be suitable and suitable for use can be replicated to overcome problems in the Pertamina other unit.